World war C : lessons from the Covid-19 pandemic and how to prepare for the next one - Gupta, Sanjay, 1969-; Loberg, Kristin (New York, NY : Simon & Schuster, 2021)
"CNN chief medical correspondent Sanjay Gupta, MD, offers an accessible, data-packed answer to our biggest questions about Covid-19: What have we learned about this pandemic and how can we prepare for--or prevent--the next one? As America's favorite frontline Covid-19 health journalist, Dr. Sanjay Gupta has barely left his primetime seat in his makeshift studio basement since the pandemic began (other than to perform brain surgery). He's had the insider of insider access to the drama's unfolding, including exclusive conversations with the world's top public health experts and behind-the-scenes scientists racing to find treatments and cures. And now he's sharing what he's learned in a book that will answer not only all our questions about what happened, but also about how our world will change in the years ahead, even once we're back to 'normal.' Gupta argues that we need to prepare for a new era where pandemics will be more frequent, and possibly even more deadly. As the doctor who's been holding America's hand through the crisis with compassion, clarity, and well-earned wisdom, he gives you the unvarnished story behind the pandemic, including insights about the novel virus's behavior, and offers practical tools to ready ourselves for what lies ahead. He answers critical questions: Can we stamp out the virus for good (and if not, how do we live with it)? Should we put our parents in a nursing home? Where should we live? What should we stockpile? What should we know before taking a trip? Does it make sense to spend more on health insurance to deal with any long-term effects? How do you decide when it's safe to go to a public pool or schedule elective surgery? What should Covid survivors know about protecting their future health? What if you become a long-hauler with chronic health challenges stemming? World War C will give you hope for the future along with real information that leaves you more resilient and secure"--
Introduction: A "pneumonia of unknown origin" -- Part 1: Humanity, we have a problem. Postmortem ; Multisystem organ failure ; Snakes ; Cows -- Part 2: Becoming pandemic P.R.O.O.F. P: plan ahead ; R: rethink and rewire risk in your brain -- O: optimize health -- O: organize family -- F: fight for the future of us.
Includes bibliographical references (pages 256-275) and index.
Keywords: COVID-19 Pandemic, 2020-2023; COVID-19 (Disease); Communicable diseases -- Prevention; Epidemics -- Prevention; Communicable Disease Control; COVID-19.; Epidemics -- prevention & control; COVID-19.